Exploring the Relationship Between Decentralised Organisational Design and Knowledge Acquisition Capacity - Cavalcanti dos Anjos, Edilene (2024)
Business firms face challenges in maintaining their sustainability in the global market. As a result, it is increasingly necessary for them to focus on ensuring sustainable performance by balancing financial, social and environmental outcomes. One of the efforts companies make to achieve sustainable organisational performance and gain a competitive advantage is by increasing their utilisation of knowledge. According to the knowledge-based view, performance differences among organisations result from their different knowledge stocks and their different capabilities for knowledge use and development. Therefore, the ability to acquire and manage knowledge internally becomes essential. It enhances the organisation’s competencies, sustains them, and contributes to achieving a competitive advantage. As a vital resource for organisational success, managing knowledge through practices is necessary. Organisational design refers to how power is distributed in an organisation. Previous research has examined the effects of knowledge management on absorptive capacity and organisational performance. However, few studies have investigated how the relationship between decentralised organisational design and knowledge acquisition capabilities works. To fill this gap, this study aims to investigate the relationship between decentralised organisational design and knowledge acquisition capability in achieving sustainable performance. A sample of 125 responses was collected from companies in the state of Santa Catarina, Brazil, through an online questionnaire. The data were analysed using partial least squares structural equation modelling applied to validate the model and test the hypothesis, through the free and open source SEMinR package of the R language. The results indicate that a decentralised organisational design has a positive and significant impact on a company’s knowledge acquisition capability. Therefore, for companies to achieve sustainable organisational performance, they must adopt appropriate organisational design methods that allow for a clear distribution of tasks and responsibilities, as well as promote learning and problem-solving and encourage the creation of a culture of knowledge sharing among employees. © 2024 Academic Conferences Limited. All rights reserved.